2005
DOI: 10.1371/journal.pcbi.0010025.eor
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Transcriptional Terminators in Bacillus subtilis and Related Species

Abstract: In prokaryotes, genes belonging to the same operon are transcribed in a single mRNA molecule. Transcription starts as the RNA polymerase binds to the promoter and continues until it reaches a transcriptional terminator. Some terminators rely on the presence of the Rho protein, whereas others function independently of Rho. Such Rhoindependent terminators consist of an inverted repeat followed by a stretch of thymine residues, allowing us to predict their presence directly from the DNA sequence. Unlike in Escher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(89 citation statements)
references
References 23 publications
6
83
0
Order By: Relevance
“…Intrinsic transcription termination mechanisms could actually compensate for the absence of Rho. In agreement with this proposal, computational searches uncovered high frequencies of putative intrinsic terminator motifs in rho-less genomes of Firmicutes (de Hoon et al, 2005), Mollicutes (Kingsford et al, 2007) and Cyanobacteria (Vijayan et al, 2011). Notable exceptions are genomes of Mycoplasma genitalium, My.…”
Section: The Rho Gene Is Absent From Cyanobacteria Mollicutes and A supporting
confidence: 67%
See 1 more Smart Citation
“…Intrinsic transcription termination mechanisms could actually compensate for the absence of Rho. In agreement with this proposal, computational searches uncovered high frequencies of putative intrinsic terminator motifs in rho-less genomes of Firmicutes (de Hoon et al, 2005), Mollicutes (Kingsford et al, 2007) and Cyanobacteria (Vijayan et al, 2011). Notable exceptions are genomes of Mycoplasma genitalium, My.…”
Section: The Rho Gene Is Absent From Cyanobacteria Mollicutes and A supporting
confidence: 67%
“…Notable exceptions are genomes of Mycoplasma genitalium, My. pneumoniae and Synechocystis PCC 6803 in which putative intrinsic terminators were only scarcely detected (de Hoon et al, 2005;Kingsford et al, 2007;Washio et al, 1998). However, it remains currently uncertain if these exceptions are due to limitations of the computational search methods or if they reflect predominance of alternative, unidentified termination mechanisms (de Hoon et al, 2005;Kingsford et al, 2007).…”
Section: The Rho Gene Is Absent From Cyanobacteria Mollicutes and A mentioning
confidence: 99%
“…Rho-independent terminators of prokaryotic genes usually contain a stem-loop structure followed by a stretch of uridylates (de Hoon et al 2005). The observation that at least one of the RNase PH domains of PNPase has affinity for U-rich stretches (i.e., the TNF-a ARE) may suggest a rationale for why the polymerase would choose to terminate these transcripts with a U-rich stretch.…”
Section: Resultsmentioning
confidence: 99%
“…However, unlike the case in E. coli, the Rho protein is dispensable in B. subtilis, suggesting a limited role for Rho-dependent termination in the latter. In fact, recent work demonstrated that more than 90% of the termination signals in B. subtilis and other Firmicutes are Rho-independent in nature [15]. Another group developed an efficient algorithm for rapid determination of Rho-independent terminators and demonstrated that outside the Firmicutes division, Rho-independent termination is also found to be dominant in the Neisseria, Vibrio and Pasteurellaceae genera [33].…”
Section: Transcriptional Terminationmentioning
confidence: 99%